ANALISIS SISTEM DAN PROSEDUR PEMBIAYAAN KONGSI PEMILIKAN RUMAHSYARIAH (KPRS)DENGAN AKAD MURᾹBAHAH PADA BNI SYARIAH KCP MIKRO KOLAKA - Abdul Haris Nasution; Reski Septiani; Muhammad Zakariah (Jurnal Ekonomi Bisnis Syariah, 2020)
This research is motivated by the BNI Syariah Bank KCP Mikro Kolaka, which is the only Islamic bank in Kolaka that is still actively receiving financing, especially for iB Griya Hasanah KPRS financing. BNI Syariah KCP Mikro Kolaka provides mortgage financing products that are in accordance with sharia principles, namely the murabahah contract. Therefore, it is necessary to know the systems and procedures carried out at BNI Syariah KCP Mikro Kolaka. This study aims to explain and analyze the implementation of the KPRS financing system and procedures based on the murᾱbahah contract applied to the BNI Syariah KCP Mikro Kolaka bank, and aims to determine whether the theories of the experts and the implementation of KPRS financing with the murbahah contract at the BNI Syariah KCP Micro Kolaka bank have been implemented corresponding. The type of research used is descriptive qualitative research that seeks to describe or provide a clear and systematic description of the research on systems and procedures for providing financing, receiving installments, and financing problems. Collecting data in the form of primary data and secondary data. This research was conducted by means of observation, interviews, and documentation to the parties concerned. The results of the study concluded that the implementation of KPRS financing systems and procedures with murabahah contracts at Bank BNI Syariah KCP Mikro Kolaka includes procedures for providing financing from filling out forms to disbursing financing, procedures for receiving installments, and resolving non-performing financing by way of restructuring has been carried out quite well, in accordance with sharia provisions and the ideas of scientists.